2018
DOI: 10.1002/mrm.27490
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flow‐encoding strength on intravoxel incoherent motion in the liver

Abstract: Purpose To study the impact of variable flow‐encoding strength on intravoxel incoherent motion (IVIM) liver imaging of diffusion and perfusion. Theory Signal attenuation in DWI arises from (1) intravoxel microvascular blood flow, which depends on the flow‐encoding strength α (first gradient moment) of the diffusion‐encoding waveform, and (2) intravoxel spin diffusion, which depends on the b‐value of the diffusion‐encoding gradient waveforms α and b‐value. Both are linked to the diffusion‐encoding gradient wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 32 publications
6
31
0
Order By: Relevance
“…One study reported ADC quantitative results in subjects with AMI, but cardiac MRI was performed 26 days after reperfusion (18). Like other researchers (15,18,28), we found that the DW trace images provided an excellent depiction of edema extent, with similar contrast to (32). Consequently, motion compensation can be seen as a mechanism to obtain a DW signal free from perfusionrelated components.…”
Section: T1 T2 and Adc Measurements Of The Myocardiumsupporting
confidence: 71%
“…One study reported ADC quantitative results in subjects with AMI, but cardiac MRI was performed 26 days after reperfusion (18). Like other researchers (15,18,28), we found that the DW trace images provided an excellent depiction of edema extent, with similar contrast to (32). Consequently, motion compensation can be seen as a mechanism to obtain a DW signal free from perfusionrelated components.…”
Section: T1 T2 and Adc Measurements Of The Myocardiumsupporting
confidence: 71%
“…Since the advent of IVIM in MRI applications, 12 the importance of diffusion time and the relevant dynamical regimes have been well recognized. 126 In the vascular compartment, the key timescale is that required to traverse a microvessel segment before changing direction. Below this timescale, the motion can be treated as "ballistic" with each segment having a single velocity vector independent of the others, while at much longer timescales, the motion is "diffusive" as the multiple changes in direction as a spin traverses the network randomize its trajectory analogously to Brownian motion in the structural compartment.…”
Section: Diffusion Time Variationmentioning
confidence: 99%
“…Alternatively, anisotropy may be modeled using von Mises (also called Fisher‐axial) distributions to describe the spatial orientation of the vasculature around a main direction, that is, the dispersion of the zenith angle of the capillary segments . Further, the stochastic process assumed in the IVIM model was shown to deviate from a Gaussian distribution within a voxel if only a few capillary segments are traversed and it was shown that the usage of gradient shapes that compensate higher‐order moments leads to a reduced signal attenuation due to perfusion …”
Section: Introductionmentioning
confidence: 99%